2021
DOI: 10.1111/btp.12933
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the importance of reproductive modes for the evaluation of altitudinal distribution patterns in tropical frogs

Abstract: Altitudinal patterns in species richness vary among taxa and are shaped by the intrinsic traits of different organisms and their response to environmental variables.We evaluated the relationship between anuran richness and elevation along local and regional altitudinal gradients within the Brazilian Atlantic Forest based on data from fieldwork (local dataset; 100-1900 m a.s.l.) and on compiled secondary information (regional dataset; 0-2300 m a.s.l.). We also tested whether frog distribution patterns were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…Microhylidae also dominate anuran species diversity in Milne Bay 21 and many mountain areas where standing water is very limited 49 . These data suggest that, as with some areas in the Neotropics 50 , high beta diversity in lineages with direct development is a key factor underpinning amphibian megadiversity in Melanesia. To address these questions further, synthetic analyses are required to better quantify the extent to which regional megadiversity in Melanesia reflects high community diversity versus species turnover, how elevation and insularity moderates these two parameters, and to what extent emergent patterns may differ from diverse frog communities in other regions such as the Neotropics.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Microhylidae also dominate anuran species diversity in Milne Bay 21 and many mountain areas where standing water is very limited 49 . These data suggest that, as with some areas in the Neotropics 50 , high beta diversity in lineages with direct development is a key factor underpinning amphibian megadiversity in Melanesia. To address these questions further, synthetic analyses are required to better quantify the extent to which regional megadiversity in Melanesia reflects high community diversity versus species turnover, how elevation and insularity moderates these two parameters, and to what extent emergent patterns may differ from diverse frog communities in other regions such as the Neotropics.…”
Section: Resultsmentioning
confidence: 62%
“…This evaluation serves three functions: to obtain further, often unpublished, information relevant to these indicators; to compare the resulting data against quantitative thresholds to determine whether a species warrants listing in any of the three ‘threatened’ categories (Vulnerable, Endangered, or Critically Endangered); and to identify further research priorities and conservation measures needed. Species accounts and maps are then reviewed post-workshop by IUCN staff in collaboration with experts to ensure accurate capture of available knowledge 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Several empirical studies on anuran species richness in different tropical and subtropical mountainous regions worldwide have documented from 16 to 60 species (Carvalho‐Rocha et al, 2021; Giaretta et al, 1999; Goyannes‐Araújo et al, 2015; Malonza & Veith, 2012; Siqueira et al, 2011, 2021; Villacampa et al, 2019; Zancolli et al, 2014). In our study, we found 70 anuran species at Poços de Caldas Plateau region.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature (temp) and humidity (humd) were recorded with a Bacharach 0012-7012 psychrometer. We recorded landscape variables that have been associated with amphibian presence (Moreira et al 2016;Ribeiro et al 2018;Siqueira et al 2021). Within a 500-m radius from the center of each sampling unit, we estimated the proportion of eight land-use and land cover types, including the following: water bodies, bare ground, urban settlements, orchards, croplands, artificial pasture, secondary and mature forest, as well as altitude (m a.s.l.).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…For these frog species, their capacity for inhabiting modified landscapes has been linked to their tolerance to high temperatures (Tracy et al 2008;Meza-Parral et al 2020). Plethodontidae salamanders and leaf litter frogs need terrestrial environments with no extreme temperature and humidity conditions that could damage the spawn of their eggs and the development of their embryos (Haddad and Prado 2005;Siqueira et al 2021). Leopard and tree frog reproduction, however, depends only on the availability of water bodies and therefore, their reproductive mode could represent an advantage in modified landscapes (Boissinot et al 2015;Nowakowski et al 2018).…”
Section: Croplands As a Predictive Variable For Species Distributionmentioning
confidence: 99%